Structural-Phase Composition of Tic/Ti Composites and Powders Obtained by Combustion of Green Mixtures Ti-C with a Titanium Excess; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 24, iss. 3 - Krinitsyn M. G. Maksim Germanovich; Korosteleva E. N. Elena Nikolaevna; Knyazeva A. G. Anna Georgievna; Sheremet E. S. Evgeniya Sergeevna (2020, 2020)
Title screen